Patient preferences for allogeneic haematopoietic stem cell transplantation: how much benefit is worthwhile from the patient’s perspective? - Leuthold, Nicolas; Cattaneo, Marco; Halter, Jörg; Hügli, Claudia; Kirsch, Monika; Petropoulou, Anna; Erlanger, Tobias E.; Gerull, Sabine; Passweg, Jakob; O’Meara Stern, Alix (Supportive care in cancer, 2021)
Oncological studies have shown that patients consider small benefits sufficient to make adjuvant chemotherapy worthwhile. We sought to determine the minimal survival benefits that patients considered enough to legitimate allogeneic haematopoietic stem cell transplantation (HCT) and the factors associated with patient preferences. One hundred eighty-four patients having previously received allogeneic HCT at our centre were included and completed a questionnaire exploring patient expectations elicited by time trade-off scenarios as well as quality of life (QoL), symptoms of graft-versus host disease (GvHD) and sociodemographic characteristics. The majority of patients considered a minimal survival benefit of at least 5 (38.6%) or 10 years (41.9%) sufficient to justify HCT, with less than 5% considering survival < 1 year sufficient to warrant HCT. In terms of minimal cure rate, a cumulative 14.8% of patients accepted cure rates below 30% and 30.6% rates below 50%. Likelihood-ratio tests were significant for the effect of age at transplant on expected minimal survival (p = 0.007) and cure rates (p = 0.0001); that is, younger patients at HCT were more likely to accept smaller survival and cure rates. Pre-transplant risk score, QoL, GvHD score and sociological factors did not seem to influence patients’ expectations. In conclusion, patient expectations of treatment were much higher than what had been reported in oncological studies. Patients who experienced HCT considered a survival superior to 1 year and cure rates above 50% sufficient to make it worthwhile. Younger patients were more likely to accept smaller benefits; no other predictors for preferences could be detected.
"Published online: 17 October 2020".- S. 3129
Gesehen am 02.09.2024